Frequency, Progression, and Current Management: Report of 16 New Cases of Nonfunctional Pancreatic Neuroendocrine Tumors in Tuberous Sclerosis Complex and Comparison With Previous Reports - Mowrey, Kate; Northrup, Hope; Rougeau, Peyton; Hashmi, S. Shahrukh; Krueger, Darcy A.; Ebrahimi-Fakhari, Daniel; Towbin, Alexander J.; Trout, Andrew T.; Capal, Jamie K.; Franz, David Neal; Rodriguez-Buritica, David (Frontiers in Neurology, 2021)
Background: Tuberous sclerosis complex (TSC) is a genetic condition that causes benign tumors to grow in multiple organ systems. Nonfunctional pancreatic neuroendocrine tumors (PNETs) are a rare clinical feature of TSC with no specific guidelines outlined for clinical management at this time. Our purpose is to calculate the frequency of nonfunctional PNETs as well as characterize the presentation, current clinical management, and assess the impact of systemic mammalian target of rapamycin (mTOR) on nonfunctional PNETs in TSC. Methods: This retrospective chart review was performed by a query of the TS Alliance's Natural History Database and the Cincinnati Children's Hospital TSC Database for patients with nonfunctional PNET. Clinical data from these two groups was summarized for patients identified to have a nonfunctional PNET and compared to previously reported cases with TSC and nonfunctional PNETs. Results: Our calculated frequency of nonfunctional PNETs is 0.65%. We identified 16 individuals, nine males and seven females, with a median age of 18.0 years (interquartile range: −15.5 to 25.5). Just over half (56.3%, n = 9) of the patients provided results from genetic testing. Six had pathogenic variants in TSC2 whereas three had pathogenic variants in TSC1. The average age at PNET diagnosis was 15.0 years (range: 3–46 years). Almost all individuals were diagnosed with a PNET during routine TSC surveillance, 56.3% (n = 9) by MRI, 12.5% (n = 2) by CT, 25% (n = 4) by ultrasound, and 6.2% (n = 1) through a surgical procedure. Follow up after diagnosis involved 68.8% (n = 11) having serial imaging and nine of the sixteen individuals proceeding with surgical removal of the PNET. Eight individuals had a history of using systemic mTOR inhibitors. Tumor growth rate was slightly less in individuals taking an mTOR inhibitor (−0.8 mm/yr, IQR: −2.3 to 2.2) than those without (1.6 mm/yr; IQR: −0.99 to 5.01, p > 0.05). Conclusions: Nonfunctional PNETs occurred at younger ages in our TSC cohort and more commonly compared to ages and prevalence reported for the general population. PNETs in patients on systemic mTOR inhibitors had lower rates of growth. The outcome of this study provides preliminary evidence supporting the use of mTOR inhibitor therapy in conjunction with serial imaging as medical management for nonfunctional PNETs as an alternative option to invasive surgical removal.